2001
DOI: 10.1364/ao.40.002632
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-induced reversible changes in the spectral characteristics of fiber Bragg gratings

Abstract: It is reported that reversible changes in the reflectivity of Bragg gratings can be induced by a change in the temperature of the grating (77 K < T < K). The changes have proved to be greater in highly doped Ge fibers than in standard fibers, whereas they could hardly be detected in hydrogenated fibers. The sign of the change for type I gratings was opposite that for type IIA gratings. The changes are likely due to a temperature-induced increase (or a decrease) in the amplitude of the refractive-index modulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In fact, reversible changes in the spectral characteristics of the fiber Bragg gratings have been observed when the temperature is increased. 19 While no refractive index changes have been detected in the SS fibers, significant corrections have been adopted when the Gedoping level is high or when the core contains B. 19 The grating coupling constants were evaluated from the reflection spectra and then plotted versus temperature.…”
Section: Fiber Bragg Gratings With Enhanced Thermal Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, reversible changes in the spectral characteristics of the fiber Bragg gratings have been observed when the temperature is increased. 19 While no refractive index changes have been detected in the SS fibers, significant corrections have been adopted when the Gedoping level is high or when the core contains B. 19 The grating coupling constants were evaluated from the reflection spectra and then plotted versus temperature.…”
Section: Fiber Bragg Gratings With Enhanced Thermal Stabilitymentioning
confidence: 99%
“…19 While no refractive index changes have been detected in the SS fibers, significant corrections have been adopted when the Gedoping level is high or when the core contains B. 19 The grating coupling constants were evaluated from the reflection spectra and then plotted versus temperature. Figure 1 summarizes the measurements performed on all the fibers.…”
Section: Fiber Bragg Gratings With Enhanced Thermal Stabilitymentioning
confidence: 99%
“…%͒ with and without hydrogen loading. 9 However, the authors observed a linear temperature response over the temperature range 296 -576 K; the nonlinear temperature response was indicated only by a single measurement at 77 K. The authors of Refs. 6 -8 also reported measurements of hydrogenated single-mode telecommunication fiber ͑SMF28 fiber͒ that suggested a nonlinear wavelength response; however, only three measurement points were presented over the temperature range 77-573 K. Therefore the origins of the nonlinearity were not clearly established; they may be previously reported nonlinearities at cryogenic temperatures 6 -8 ; alternatively, Flockhart et al 10 have observed changes in the temperature sensitivity that are due to buffer-recoating effects.…”
Section: Introductionmentioning
confidence: 98%
“…Change in surrounding temperature impacts the effective grating period by either linear thermal expansion of the material and/or a change in the fiber's refractive index due to temperature (thermo-optic effect). [10,14,15] Existing literature indicates the FBG show a temperature dependent shift of 10 pm/K around 293 K. [10] There is some disagreement over the temperature dependent behavior and measurement uncertainties with different reports suggesting the thermal response may be linear [16,17] or quadratic [18].…”
Section: Introductionmentioning
confidence: 99%